IMPLEMENTING THE VALUE OF RELIGIOUS MODERATION IN EARLY CHILDHOOD THROUGH LEARNING BASED ON LOCAL WISDOM AT THE PANGLIMA SEMESTA KINDERGARTEN IN MEDAN - Rahman, Mhd Habibu; Lubis, Sofni Indah Arifa; Mahira, Ulfa (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to examine the application of the value of religious moderation in early childhood as an effort to form balanced character and morality. In the context of globalization and cultural plurality, children are faced with various influences that can shape their thinking and behavior patterns. Therefore, this research focuses on implementing the value of religious moderation as a basis for guiding children to understand and appreciate religious teachings wisely based on learning based on local wisdom. This research method is qualitative involving observation and interviews. Data analysis by condensing data, displaying data and drawing conclusions. The research results show that the application of the value of religious moderation makes a positive contribution to children's character development. Children show a better understanding of religious values and are able to apply them in everyday life. In addition, the role of teachers and parents as role models in practicing the value of religious moderation is a key factor in the success of this implementation. The findings of this research provide practical implications for educators, parents and policy makers to improve approaches to religious education at the early age level. By strengthening the value of religious moderation with learning based on local wisdom, it is hoped that children can grow into individuals who are responsible, tolerant, and have a deep understanding of religious diversity in society and love Indonesian culture.